Municipal solid waste management strategies : impact of waste generation behaviours in rural and urban communities : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Environmental Technology, Massey University, Palmerston North, New Zealand - Jorgensen, Lone Morris (Massey University, 1996)
The waste generation characteristics of households was investigated in relation to waste management principles and philosophies in urban and rural New Zealand, to evaluate current practices regarding municipal solid waste at the national, district- and city council level. Two selected councils, one rural and one urban, were studied in detail. A household sample from each council was surveyed to establish the trends in household waste generation. The results from these surveys were compared using statistical analyses. The initial results suggested that rural and urban households show significant differences. Further analysis, involving a detailed case study of a rural settlement, suggests that these differences arise from the economic signals received from the council and not from population structure and culture, although some subgroups in the population appear to ignore these signals. A householders' survey analysis of waste designated for recycling proved to be unreliable and difficult to interpret. This was caused by the public's general inability to interpret plastic recycling numbers for correct sorting, and to measure volume and weight correctly. Conclusions were reached with regard to paper and household organic waste. While there appears to be little difference in the amounts produced per person in either the wards or between the councils, a proportional analysis suggests that middle income households compost and recycle more than low income households. This has been interpreted as a possible effect of multi-family dwellings and the type of education material used to deliver the recycling messages. An analysis of household waste delivered to the landfills by the collection system in the two selected councils shows that the rural household waste has a higher proportion of organics and a lower proportion of paper waste than do the urban households. The rural households also compost less and visit the landfill more. This supports the conclusion that economic signals dictate the waste generation behaviours of households. The effectiveness, in light of sustainability and economics, of the systems in place in New Zealand were studied and compared with international trends in waste management systems. Economic signals appear to be a strong motivator for individual waste generation behaviours. Composting as a potential waste minimisation system for New Zealand was also investigated. Green waste composting appears to be an economically viable method of waste minimisation for urban and some rural councils. The data collected in the surveys suggest that home composting of household organics can offer a solution to reduce waste from the household source. The methods and effects of implementing this as a strategy require more study.
Keywords: Refuse and refuse disposal; Municipal solid waste management; New Zealand